Disaster for hire - Dixon, Franklin W. (Simon & Schuster New York, 1999)
Disaster for Hire is a captivating novel that follows the misadventures of an unconventional freelance disaster manager, Max, who is hired to resolve a series of escalating crises for various clients. From a collapsing wedding to a failing product launch, Max$1 (Bs unique skills in chaos management bring both hilarity and heart to the unfolding drama. However, when a seemingly routine assignment spirals into a much larger catastrophe, Max must rally an eccentric team of specialists to avert disaster and restore order. The story explores themes of resilience, teamwork, and the unpredictability of life, delivering a humorous yet insightful look at how we handle chaos in our personal and professional lives.s